Pola Perubahan Protein Koro Benguk (Mucuna pruriens) Selama Fermentasi Tempe Menggunakan Inokulum Raprima - Novia Aristi Rahayu; Muhammad Nur Cahyanto; Retno Indrati (agriTECH, 2019)
Tempe is a nutritious healthy food because it contains bioactive compounds that are beneficial to human health. This product is good for those who are vegetarian. During the fermentation process, fungi produce proteases that break down the velvet bean’s proteins into protein fragments or peptides which have functional properties. The fungus strain and the duration of incubation time will affect the bioactive peptides formed. This study aimed to determine the effect of tempe inoculum on changes in peptide concentration and protein patterns during fermentation. The results showed that proteolytic activity increased rapidly at the beginning of tempe fermentation and reached its optimum activity in 96 h fermentation period (0.046 U/mL). The pH of tempe changed from 7.01 then decreased to 5.92 in 30 h incubation, after that it increased again to 7.25 at the end of fermentation time (120 h). Peptide concentration increased with increasing fermentation time. The degree of hydrolysis increased rapidly until 24 h of incubation, then began to be stable until 96 h of incubation (reaching the hydrolysis degree of 46.31%). SDS PAGE patterns showed the formation of proteins/peptides with a molecular weight of <25 kDa as a result of hydrolysis of velvet bean protein during tempe fermentation using Raprima inoculum